Middle school students’ perceptions and beliefs about the National School Lunch Program - Keller, Jessica (Kansas State University, 2013)
The National School Lunch Program (NSLP) seeks to provide nutritionally balanced, low-cost or free lunches to more than 31 million children daily. With the recent increase in childhood obesity, school nutrition programs must follow strict nutrient guidelines in meal preparation. As nutrient requirements have changed, participation in the NSLP has also decreased, especially among older students. To recover lost revenue, many schools offer al a carte items or other snack items often characterized as high in calories, fat, and carbohydrates. The NSLP provides meals with a balance of vegetables, fruits, whole grains, and low-fat and fat-free milk. Some research suggests that unintentional stereotypes or social stigmas exist about the NSLP program among participants. Al a carte and vending machine food options have influenced these stereotypes and in some cases have deterred students from participating in the NSLP. Research about stigma association with the NSLP is scarce and not current. This study investigated if social stigmas exist about the NSLP and their influence on student participation. Middle school students in Kansas comprised the population for this study. A survey instrument was drafted using themes identified from existing research. In addition to demographic variables, the survey contained statements that examined factors that motivate and de-motivate students from participating in the NSLP, and statements about social stigmas and peer influence. A panel of child nutrition program experts and a pilot study with middle school students were used to refine and validate the survey. The survey was distributed to middle school students in thirteen Family and Consumer Science classes in Kansas. A total of 559 students responded to the survey for a response rate of 48%. This study found that few of the motivator statements correlated with participation in the NSLP. However, preference for snack foods was identified as the largest deterrent in respondent participation. Few new social stigmas were identified, but significant variations were found when examining variations between some demographic variables. Respondents who were female, older in age and grade level, frequently ate school lunch, and attended large schools with a high number of students receiving lunch at a free and/or reduced price were more aware of social stigmas and more greatly impacted by the actions of their peers. In contrast, qualitative data showed that some respondents are greatly influenced by peers and the fear of stigmatization.
Keywords: National School Lunch Program; School nutrition program; Participation; Nutrition (0570)